2019
DOI: 10.1021/acs.jpcc.8b11840
|View full text |Cite
|
Sign up to set email alerts
|

CO, CO2, and H2Interactions with (0001) and (001) Tungsten Carbide Surfaces: Importance of Carbon and Metal Sites

Abstract: In this work, a systematic study on the adsorption of atomic and molecular hydrogen and carbon oxides on cubic (001) and hexagonal (0001) WC surfaces by periodical density functional theory is reported. Calculations have been performed by employing the Perdew–Burke–Ernzerhof exchange correlation functional with van der Waals corrections to account for the dispersive force term. In addition, dipole corrections were applied for W- and C-terminated hexagonal WC(0001) surfaces. Good agreement is found between calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 78 publications
1
35
0
Order By: Relevance
“…Hydrogenation reactions are common in many industrial processes, e.g., in the petrochemical plastic generation, the saturation of vegetable oils polyunsaturated fat acids in food chemistry, or in environmental chemistry, converting greenhouse carbon dioxide (CO 2 ) into greener chemicals . Hitherto, hydrogenations have been mostly catalyzed using scarce and expensive Pt-group metals. , During the last decades, transition Metal Carbides (TMCs) have emerged as an alternative, often displaying superior activities and selectivities for a wide variety of relevant hydrogenation reactions. …”
mentioning
confidence: 99%
“…Hydrogenation reactions are common in many industrial processes, e.g., in the petrochemical plastic generation, the saturation of vegetable oils polyunsaturated fat acids in food chemistry, or in environmental chemistry, converting greenhouse carbon dioxide (CO 2 ) into greener chemicals . Hitherto, hydrogenations have been mostly catalyzed using scarce and expensive Pt-group metals. , During the last decades, transition Metal Carbides (TMCs) have emerged as an alternative, often displaying superior activities and selectivities for a wide variety of relevant hydrogenation reactions. …”
mentioning
confidence: 99%
“…These materials are normally regarded as available and economic potential substitutes to catalysts based on scarce and expensive Pt‐group late transition metals, displaying similar or even superior catalytic activities and selectivities 218 . One appealing aspect of TMCs concerning CO 2 conversion is that such materials display significantly strong CO 2 adsorption energies, 219 e.g., ranging from −0.61 eV for the C‐terminated orthorhombic β‐Mo 2 C (001) surface, to −3.27 eV for Mo‐terminated β‐Mo 2 C (001) surface, 220 as estimated by DFT means using slab supercell models and the PBE density functional 132 . Regardless of the TMC crystal structure, a common feature is that CO 2 gets not only strongly adsorbed, but also significantly activated; this is, with a bent geometry, see Figure 5(a), and displaying a negative Bader charge 204…”
Section: Representative Examples Of Computational Studies For Co2 Conversionmentioning
confidence: 99%
“…233 Indeed, the theoretical modeling and calculated reaction free energy profile at 600 K with equal pressures of 0.2 bar of both CO 2 and H 2 reactants, see Figure 5(b), revealed that all surfaces are well capable of adsorbing, activating, and easily breaking CO 2 , with energy barriers below 0.59 eV, and specially low for Mo-terminated surfaces, in line with previous results on tungsten carbides with barriers as low as 0.71 eV for Wterminated surfaces. 219 Similarly, H 2 easily dissociates on all the explored TMCs 219,234 indicating that they may be useful for CO 2 conversion to methanol, formic acid, or CO in an H-assisted mechanism.…”
Section: Transition Metal Carbidesmentioning
confidence: 99%
“…When the metal/carbon ratio is close to one, CO and methanol are the main products for the hydrogenation of CO 2 over a carbide catalyst (Dubois et al, 1992;Xu et al, 2014;Posada-Pérez et al, 2016). Theoretical calculations have shown that, in general, CO 2 binds well on MC(001) surfaces (M = Ti, Mo, Zr, Hf, Nb, Ta, Hf, and W) (Vidal et al, 2012;Posada-Perez et al, 2014;Posada-Pérez et al, 2016;Kunkel et al, 2016;Dixit et al, 2017;Koverga et al, 2019). Figure 11 shows results of DF calculations for the bonding geometry of the CO 2 molecule on plain TiC(001) (Vidal et al, 2012).…”
Section: Co 2 Hydrogenation To Methanol and Comentioning
confidence: 99%